2007
DOI: 10.1007/s11242-006-9094-z
|View full text |Cite
|
Sign up to set email alerts
|

Pore space network characterization with sub-voxel definition

Abstract: Morphological measurements in 3D for pore space characterization (connectivity, pore-body/throat classification, shape factors, virtual fluid intrusion) are based on computed intensive digital-thinning operations for skeletonization and medial axis extraction from 3D digital images. We present an alternative method that is measurably faster and allows sub-voxel definition of the pore space network. The method allows extracting-based on morphological considerations only-the centered and shortest stream-lines-i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Particular attention is paid to avoid the removal of clays in the pore space of the digital sample. Some preliminary findings on the digital volume of this sample calculated with a network model are reported elsewhere (Schena and Favretto 2007), where it is shown that the permeability values are of the same order of magnitude as determined from experimental laboratory tests.…”
Section: Analysis Of a Real Porous Samplementioning
confidence: 67%
See 2 more Smart Citations
“…Particular attention is paid to avoid the removal of clays in the pore space of the digital sample. Some preliminary findings on the digital volume of this sample calculated with a network model are reported elsewhere (Schena and Favretto 2007), where it is shown that the permeability values are of the same order of magnitude as determined from experimental laboratory tests.…”
Section: Analysis Of a Real Porous Samplementioning
confidence: 67%
“…14 and the hydraulic network result (Schena and Favretto 2007) in Table 6. Both the computed results and Carman's correlation overestimate the experimental measurement.…”
Section: Analysis Of a Real Porous Samplementioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40]108] do not necessarily reflect properties of particular rocks. Although advanced algorithms for generating irregular pore networks which would characterize the pore space geometry of a desired particular rocks have been developed [70,90], this task is challenging and apparently no routine approach is available. Even in a regular network, the geometry of the cross-sections of the throats can produce unexpected results [8].…”
Section: Discussionmentioning
confidence: 99%
“…Running flow simulations directly on the digital image bypasses the challenging task of building a network characterizing the pore space geometry of the sample under consideration [78,79]. Capillary equilibrium does not uniquely define the fluid distribution in the pore space.…”
Section: Flow Simulation and Evaluation Of Permeabilitymentioning
confidence: 99%